2010
DOI: 10.1016/j.jfa.2010.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Concentration in a thin Euclidean shell for log-concave measures

Abstract: A weak version of a conjecture stated by Kannan, Lovász and Simonovits claims that an isotropic logconcave probability μ on R n should be concentrated in a thin Euclidean shell in the following way:where κ = 1/2 and c and C are positive absolute constants. For κ = 1/10.02, this inequality has been established by Klartag. By combining different approaches introduced by Klartag and by Guédon, Paouris and the author, we improve this result by showing that the inequality (1) holds with κ = 1/8.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 11 publications
(11 reference statements)
2
37
0
Order By: Relevance
“…More than two decades after being put forth, the KLS conjecture is still unresolved, and the presently best known (dimension-dependent) estimate on C = C n in (1.4) is C n ≤ Cn 1/4 , obtained very recently (after this work was posted on the arXiv) by Y. T. Lee and S. Vempala [52] by employing the remarkable Stochastic Localization method of R. Eldan [23]; previous contributions include those by KLS [37], S. Bobkov [11], B. Klartag [40,41], B. Fleury [26] and O. Guédon and Milman [34]. The conjecture has been confirmed (uniformly in n) for unit-balls of ℓ n p (by S. Sodin [67] when p ∈ [1, 2] and R. Lata la and J. Wojtaszczyk [49] when p ∈ [2, ∞]), the simplex by F. Barthe and P. Wolff [7], convex bodies of revolution by N. Huet [36], convex sets of bounded volume-ratio constructed in a certain manner from log-concave measures which satisfy the conjecture [46], linear images and Cartesian products of these subclasses (see for the latter) and various perturbations thereof [56,59].…”
Section: Previously Known Resultsmentioning
confidence: 99%
“…More than two decades after being put forth, the KLS conjecture is still unresolved, and the presently best known (dimension-dependent) estimate on C = C n in (1.4) is C n ≤ Cn 1/4 , obtained very recently (after this work was posted on the arXiv) by Y. T. Lee and S. Vempala [52] by employing the remarkable Stochastic Localization method of R. Eldan [23]; previous contributions include those by KLS [37], S. Bobkov [11], B. Klartag [40,41], B. Fleury [26] and O. Guédon and Milman [34]. The conjecture has been confirmed (uniformly in n) for unit-balls of ℓ n p (by S. Sodin [67] when p ∈ [1, 2] and R. Lata la and J. Wojtaszczyk [49] when p ∈ [2, ∞]), the simplex by F. Barthe and P. Wolff [7], convex bodies of revolution by N. Huet [36], convex sets of bounded volume-ratio constructed in a certain manner from log-concave measures which satisfy the conjecture [46], linear images and Cartesian products of these subclasses (see for the latter) and various perturbations thereof [56,59].…”
Section: Previously Known Resultsmentioning
confidence: 99%
“…Therefore, to prove the lower bound for 0 < p < ∞, it is sufficient to consider K in isotropic position. Let L K be the isotropic constant of K. By the thin shell estimate of O. Guédon and E.Milman [22] (see also [15,42]), we have with universal constants c and C, that for all t ≥ 0,…”
Section: Proofsmentioning
confidence: 98%
“…In a breakthrough, Eldan [35] showed that the thin shell conjecture is in fact equivalent to the KLS conjecture up a logarithmic factor (see Theorem 35). [52] n 4/10 2010/Fleury [39] n 3/8 2011/Guedon-Milman [44] n 1/3 2016/Lee-Vempala [65] n 1/4 Table 1: Progress on the thin shell bound.…”
Section: Thin Shell To Central Limit Theoremmentioning
confidence: 99%